AN ANALYSIS OF THE OPEN SKIES POLICY AND ITS EFFECTS ON THE TOURISM INDUSTRY IN MEXICO - Tello Contreras, Juan Manuel (Journal of Tourism, Sustainability and Well-being, 2017)
The New Bilateral Air Services Agreement between Mexico and the United States specifies that all cargo and passenger aircraft of both countries will allow any airline to flight from one point in the neighboring country and make a stop at another airport to pick up and unload passengers or cargo in the airports of both countries. This paper analyzes the 2016 “open skies agreement” between United States of America and Mexico and its expected effects on the Mexican airlines industry. After reviewing the evidence and analyzing the performance of Mexican and US airlines, it is inferred that the bilateral agreement will increase foreign investment in Mexico due to the entry into the market of a greater number of North American passenger and cargo airlines, but above all, will increase international trade in goods and services, being the United States airline industry the one that will benefit the most due to the superiority of the air fleet over the Mexican. The theoretical Cournot model adapted from Alves and Forte (2015) indicates that airlines that do not have the ability to compete for new routes will be adversely affected, their profits will decrease, an assertion that contradicts the expected effects in the literature.